Plasma lipid peroxide levels in an urbanized Micronesian population: Nauru - Yagi, K; Matsuoka, S. (Nagoya Univ. (Japan). Faculty of Medicine); Linnane, A.W; Zimmet, P (Journal of Nutritional Science and Vitaminology, 1981)
Plasma lipid peroxide levels of 419 inhabitants of Nauru, where a high prevalence of obesity is occurring, were measured. The plasma lipid peroxide level was 4.03±1.94 nmol/ml in subjects 20-24 years and rose to a peak of 5.78±3.21 in subjects 35-44 years'. The values obtained with Nauruans are significantly higher than those of healthy Japanese people and the peak found in the former was shifted to a younger age than in the Japanese.